Jabulani : freedom of the airwaves : towards democratic broadcasting in South Africa - conference report - Balch, Jeff; Jansen, Martin; Janns, Frederique (Amsterdam: African European Institute, 1991)
"Conferentie gehouden te Doorn, augustus 1991"